Agriculture and structural transformation : economic strategies in late-developing countries - Johnston, Bruce F.; Kilby, Peter (New York : Oxford University Press, 1975)
The analysis in this work is directed at those long-term alterations in economic structure which will, among other consequences, transform the relationship between agricultural productivity and population increase so as to permanently banish the Malthusian theory.
Includes bibliographical references and indexes.
SJU 22/01/2019
Loans
Keywords: Agriculture